Disability, parents and siblings with a migratory background. Sociocultural dynamics and inclusive perspectives - Emanuela Bini (University of Bologna, 2022)
What happens when a disabled child is born in a migrant family? How do relationships and roles change in a family committed to assist a disabled child in a foreign country? How do migrants approach to new educational and rehabilitative models that depart from their traditional educational model? Parents and siblings of a disabled child often face linguistic, economic and housing difficulties that are typical of the migratory experience; however they face also further challenges for socioeducational integration in order to define linguistic and cultural identity and educational models imprited to plurality. In this article the Author tries to give an answer to several questions by referring to several researches in sociology, cultural anthropology, ethnopsychiatry, intercultural pedagogy, special pedagogy that investigated the interwing of disability and migration and also the role of Institutions, social health services, school and voluntary associations asked to individuate strategies and resources to define effective interventions to support inclusive process of migrant families with disabled children.